2005
DOI: 10.1038/sj.gt.3302548
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of efficient transfection of the nasal airway epithelium by hypotonic shock

Abstract: The main barrier to gene transfer in the airway epithelium is the low rate of apical endocytosis limiting naked DNA uptake. Deionized water is known to stimulate the exocytosis of numerous intracellular vesicles during hypotonic cell swelling, in order to expand plasma membrane and prevent cell lysis. This is followed by the phase of regulatory volume decrease (RVD), during which the excess plasma membrane is retrieved by intensive endocytosis. Here we show that the more hypotonic the DNA solution, the higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Huang et al demonstrated that hypotonic shock enhanced uptake of plasmid DNA by nasal epithelium in vivo via the regulatory volume decrease (RVD) mechanism [317]. Specifically, they showed that sodium- and sucrose-based hypotonic vehicles provided enhanced transgene expression in the mouse nasal epithelium compared to isotonic vehicles with the greater effect observed with lower osmolality.…”
Section: Strategies To Overcome the Barriers To Inhaled Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al demonstrated that hypotonic shock enhanced uptake of plasmid DNA by nasal epithelium in vivo via the regulatory volume decrease (RVD) mechanism [317]. Specifically, they showed that sodium- and sucrose-based hypotonic vehicles provided enhanced transgene expression in the mouse nasal epithelium compared to isotonic vehicles with the greater effect observed with lower osmolality.…”
Section: Strategies To Overcome the Barriers To Inhaled Gene Therapymentioning
confidence: 99%
“…During this endocytic process, particulates, including inhaled gene vectors, in the vicinity of the apical membrane can be taken up by epithelial cells. The RVD effect has been shown to last up to 30 minutes [317, 319]. Potential safety concern resulting from hypotonic shock would need to be addressed before clinical implementation of this approach.…”
Section: Strategies To Overcome the Barriers To Inhaled Gene Therapymentioning
confidence: 99%
“…First, we applied hypotonicity mucosally in order to imitate mucosal osmotic changes encountered by simple epithelial cells in a physiologic or therapeutic setting (25)(26)(27). Mucosal hypotonicity of 18.4% elicited a robust and sustained rise in the I sc (DI sc ), with the current amplitudes and channel-inhibitor sensitivities being similar to those in DI sc activated by forskolin, a classic activator of CFTR ( Fig.…”
Section: Mucosal Hypotonicity Activated Apical Cftr In Calu-3 Epithelmentioning
confidence: 99%
“…Previous studies have suggested that hypotonic solutions can increase gene transfer efficacy. 36 Thus, we cannot exclude that the control animals (GL67/pDNA) showed values higher than if we had been able to use saline as the diluent for this group. To characterize the magnetic particles further, particle sizing was attempted but the polydispersity index indicated that all solutions were too heterogeneous in size to provide accurate data.…”
Section: Figurementioning
confidence: 99%